IMPLEMENTASI KEBIJAKAN PENGELOLAAN KEUANAGAN DESA WAITINA KECAMATAN MANGOLI TIMUR KABUPATEN KEPULAUAN SULA - UMAKAMEA, MUHAMMAD SANIF; ROMPAS, WILSON; PALAR, NOVIE ANDERS (Sam Ratulangi University, 2017)
Abstract: This research aims to know the implementation of the financial management policies of the villageof Waitina Sub-district Mangoli timur Regency Sula Islands. This research uses theories of Edward III'spolicy implementation with communication indicators, resources, disposition and bureaucratic structure.This study uses qualitative methods with an informant as much as 10 people comprising the headof BPD, the village chief, officials of the customs of the village, the village Authorities and society.Research results show that financial management of the village of waitina in General has alreadydone with effective but in demensi resources and disposition or attitude of the executor not optimal so thatthere is also an inhibitor of factor or constraint in financial management of the village. The dimensions ofthe resources and the attitude of the authorities of the village should be increased in order to improve thequality of the implementation of the financial management of the village in the village of Waitina, SulaIslands RegencyKeywords: Financial Management Policy Implementation